The correlation between multimodal radiomics and pathology about thermal ablation lesion of rabbit lung VX2 tumor - Chen, Jin; Yan, Yuan; Lin, QingFeng; Chen, Jian; Chen, Jie; Lin, ZhengYu (Frontiers in Oncology, 2022)
Objective To explore the correlation of CT-MRI pathology with lung tumor ablation lesions by comparing CT, MRI, and pathological performance of rabbit lung VX2 tumor after thermal ablation. Methods Thermal ablation including microwave ablation (MWA) and radiofrequency ablation (RFA) was carried out in 12 experimental rabbits with lung VX2 tumors under CT guidance. CT and MRI performance was observed immediately after ablation, and then the rabbits were killed and pathologically examined. The maximum diameter of tumors on CT before ablation, the central hypointense area on T2-weighted image (T2WI) after ablation, and the central hyperintense area on T1-weighted image (T1WI) after ablation and pathological necrosis were measured. Simultaneously, the maximum diameter of ground-glass opacity (GGO) around the lesion on CT after ablation, the surrounding hyperintense area on T2WI after ablation, the surrounding isointense area on T1WI after ablation, and the pathological ablation area were measured, and then the results were compared and analyzed. Results Ablation zones showed GGO surrounding the original lesion on CT, with a central hypointense and peripheral hyperintense zone on T2WI as well as a central hyperintense and peripheral isointense zone on T1WI. There was statistical significance in the comparison of the maximum diameter of the tumor before ablation with a central hyperintense zone on T1WI after ablation and pathological necrosis. There was also statistical significance in the comparison of the maximum diameter of GGO around the lesion on CT with the surrounding hyperintense zone on T2WI and isointense on T1WI after ablation and pathological ablation zone. There was only one residual tumor abutting the vessel in the RFA group. Conclusions MRI manifestations of thermal ablation of VX2 tumors in rabbit lungs have certain characteristics with a strong pathological association. CT combined with MRI multimodal radiomics is expected to provide an effective new method for clinical evaluation of the immediate efficacy of thermal ablation of lung tumors.